Klaas Koen: Identity and belonging in the Berlin Mission Society during the late nineteenth century (Historia, 2021)
Klaas Koen should not have belonged. Of Khoisan descent, he wasn’t German, he wasn’t white, and he came from the “wrong” class background to be a missionary. (Indeed, as Elizabeth Elbourne has demonstrated, by the 1830s, many white settlers in the Cape – and some missionaries – saw the Khoikhoi as being sub-human and dismissed missionary notions of the “reclaimability” of those who converted to Christianity. 1) However, after his training in Berlin, Koen became so German that he sat in tears on his first Christmas at his own mission station in South Africa. There was no Christmas tree decorated with candles in German style. Koen died a “blessed death” in the service of the Berlin Mission Society. A tract was produced about his life. This article examines the life history of this man and explores why the mission society treated him, wrote about him, and remembered him as they did. It also suggests some reasons why the young missionary may have made the choices that he did. It concludes with an examination of some aspects of his posthumous identity.
Keywords: Klaas Koen; Khoisan descent; missionary; many white settlers in the Cape; Khoikhoi; Christianity; mission society